Advances in materials science for ocular diseases induced by cardiovascular risk factors - Chen, Peiwen; Zheng, Bo; Wang, Peng; Liu, Hao; Pei, Haifeng (Frontiers in Bioengineering and Biotechnology, 2025)
Cardiovascular risk factors such as hypertension, hyperlipidemia, and hyperglycemia are closely associated with ocular diseases including glaucoma, diabetic retinopathy, and dry eye syndrome. These conditions are characterized by microvascular damage, hemodynamic alterations, and pathological neovascularization, ultimately leading to significant visual impairment. Traditional treatments often suffer from limitations, such as invasiveness and poor target specificity, highlighting the urgent need for innovative therapeutic approaches. Recent advancements in biomaterials have substantially improved therapeutic efficacy, particularly in the areas of targeted drug delivery, smart sensors, and tissue repair. Smart sensors like contact lenses enable continuous monitoring of intraocular pressure, enhancing glaucoma management. Nanotechnology and drug delivery systems improve drug targeting and bioavailability, enhancing anti-angiogenic therapies. Additionally, biocompatible materials and nanomaterials have shown promise in promoting retinal and optic nerve repair, facilitating neural regeneration and reducing aberrant neovascularization. Despite ongoing challenges, the rapid evolution of materials science holds transformative potential for developing more effective and personalized treatments for ocular diseases.